Immune exhaustion in chronic chagas disease: Pro-inflammatory and immunomodulatory action of il-27 in vitro - Natale, Maria Ailen (2021)
In chronic Chagas disease, Trypanosoma cruzi-specific T-cell function decreases over time, and alterations in the homeostatic IL-7/IL-7R axis are evident, consistent with a process of immune exhaustion. IL-27 is an important immunoregulatory cytokine that shares Tcell signaling with IL-7 and other cytokines of the IL-12 family and might be involved in the transcriptional regulation of T-cell function. Here, we evaluated the expression and function of IL-27R in antigen-experienced T cells from subjects with chronic Chagas disease and assessed whether in vitro treatment with IL-27 and IL-7 might improve T. cruzi-specific polyfunctional T-cell responses. In vitro exposure of PBMCs to T. cruzi induced a downregulation of IL-27R in CD4+ T cells and an upregulation in CD8+ T cells in subjects without heart disease, while IL-27R expression remained unaltered in subjects with more severe clinical stages. The modulation of IL-27R was associated with functional signaling through STAT3 and STAT5 and induction of the downstream genes TBX21, EOMES and CXCL9 in response to IL-27. In vitro treatment of PBMCs with IL-27 and IL-7 improved monofunctional and polyfunctional Th1 responses, accompanied by the induction of IL-10 and Bcl-2 expression in subjects without heart disease but did not improve those in subjects with cardiomyopathy. Our findings support the process of desensitization of the IL-27/IL-27R pathway along with disease severity and that the pro-inflammatory and immunomodulatory mechanisms of IL-27 might be interconnected.